DISHARMONY IN MINERAL AND COAL MINING REGULATION IN ACEH: A Critical Review of the Basic UUPA, UU Minerba and MoU Helsinki - Ridwansyah, Muhammad; Abidin, Zainal; Zakyyah (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2026)
This study examines the authority of the Aceh Government in the mineral and coal mining sector from the perspective of two main legal instruments: the Mineral and Coal Mining Law (UU Minerba) and the Aceh Governance Law (UUPA). The method used is normative juridical research with a legislative, conceptual, and comparative approach. First, the authority of the Aceh Government in the mineral and coal mining sector has been normatively recognized through Article 173A of the Minerba Law, which emphasizes that the provisions of the law apply to Aceh Province as long as they are not specifically regulated in laws governing regional specialties. This provision positions the UUPA as a lex specialis that should be the primary reference in mining management in Aceh, so that this authority cannot simply be transferred to the Central Government. Second, although the UUPA is normatively recognized as a special regulation, the implementation of the UUPA in practice has the potential to override the authority of the Aceh Government. There is a legal tension between the UU Minerba as a national regulation and the UUPA as a special law that has not been explicitly resolved. This condition creates legal uncertainty that is detrimental to Aceh, because the Central Government tends to interpret mining authority in a centralistic manner. Third, the management of mineral and coal mining in Aceh should be built on two main foundations: the Helsinki MoU of August 15, 2005, and the principles of the Unitary State of the Republic of Indonesia (NKRI). The Helsinki MoU serves as the political and legal basis for Aceh to manage its natural resources independently and with dignity. Therefore, mining management in Aceh should ideally adhere to the spirit of asymmetric decentralization mandated in the Helsinki MoU, while upholding the sovereignty of the Unitary State of the Republic of Indonesia. This article recommends that mining authority be clarified in the Basic UUPA Law, that the Mining Law be directed toward strengthening Aceh's autonomy, and that the Aceh Government consistently adhere to the spirit of the Helsinki MoU as the basis for equitable natural resource management.